Editorial Preface on the Proceedings of the 6th International Conference on Recent Advances in Materials, Minerals & Environment in Penang, Malaysia. (2019) - Sreekantan, S.; Lockman, Z.; Saharudin, K.A.; Taib, R.M.; Khimi, S.R.; Baharun, N.; F. S. Hashim, S.
Abstract: The 6th International Conference on Recent Advances in Materials, Minerals & Environment (RAMM 2018) took place in Penang, Malaysia from 27 - 29 November 2018. The conference covered three main topics: Advances in Materials Science and Engineering, Innovations in Polymeric Materials, and Progress in Mineral Resources and Environment Science for Sustainable Development. This book is a compilation of selected papers presented during RAMM 2018. The conference had gathered international experts to discuss on the advances in materials, nanomaterials, polymer, mineral resources and environment science and perspectives of future developments of each of the topic. All contributions in this book concentrated around the most recent innovations, concerns, and challenges encountered by materials and mineral resources researchers in tackling global issues related to pollution, environment and sustainabilitye.